Environmental Education and Sustainability in the Installation of Recycling Points in the city of Itaquaquecetuba/SP - Moreira , Paulo Roberto S.; Ramos , Heidy Rodriguez; Gallego, Jorge L. (Electronic Journal "Fórum Ambiental da Alta Paulista", 2025)
Objective – This study aims to analyze the impacts of installing recycling points on environmental awareness and reducing irregular waste disposal in the city of Itaquaquecetuba. Methodology – A qualitative research approach was adopted, including a literature review and documentary analysis, to evaluate the implementation and effects of recycling points in the city. Originality/Relevance – The research highlights the importance of environmental education as a tool to promote sustainability, highlighting the role of recycling points in changing behaviors related to waste disposal. Results – The results indicate that the installation of recycling points in Itaquaquecetuba contributed to a reduction in irregular waste disposal while strengthening awareness of recycling and proper material management. Theoretical/Methodological Contributions – The study integrates theories on waste management and environmental education, using document analysis to understand the impact of recycling points on social and environmental transformation. Social and Environmental Contributions – The study concludes that environmental education, combined with the implementation of recycling points, can positively impact sustainability promotion and environmental protection by engaging the community in responsible waste management.